Characteristics and outcomes of patients with COVID-19 in an intensive care unit of a community hospital; retrospective cohort study - Jorge Cedano; Emilio Fabian Corona; Melissa Gonzalez-Lara; Melvin Santana; Islam Younes; Sarah Ayad; Andrew Kossack; Anam Purewal; Raja Pullatt (Greater Baltimore Medical Center, 2021)
Background: The limited data available so far has shown a high mortality rate among COVID-19 patients admitted to the ICU. Possible risk factors for poor outcomes in this type of patients need to be analyzed so we can identify strategies to reduce mortality. Objective: Characterized the COVID-19 experience in Community hospital ICU. Methods: Single center retrospective cohort study involving all adult patients admitted to the ICU with severe COVID-19 infection. Results: 132 patients were admitted to ICU during the study period. There was a preponderance for males and the most common ethnicity was Hispanic. The overall mortality was 69%, and mortality after intubation was 76%. In the multivariable analysis older Age (OR = 15.7), Obesity (OR = 2.92) and Mechanical Ventilation (OR = 12.0) were found to be a significant independent risk factor for increased mortality. Conclusion: Our study confirms the high mortality rate in patients critically ill with COVID-19 requiring ICU care especially among older age group, mechanically ventilated and obese patients. Overall outcomes are comparable to larger tertiary care centers. Our findings highlight the need to plan for optimal resource allocation and tailoring therapies to target the disease so as to improve outcomes.